(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2015)
The article primarily describes the author’s relationship with Ludovico Quaroni at the time of ‘the Workshop’ set up in the Design Institute (Istituto di Progettazione) of the Faculty of Architecture in Rome in the early seventies, and especially his involvement with the ‘Glossary’ of specialist terms, which led to certain important teaching commitments carried out by Quaroni in the years that followed. During this period the question of Order took shape and was organised and inter-related with the themes of design research and contemporary aesthetics.